4 - La place et le rôle des oeuvres d’art dans le développement africain : cas du Congo-Brazzaville - Louis Kouéna Mabika, (Africa Media Review, 2005)
The purpose of this paper is to show the role and importance of culture in the development process, and also to show the impact of works of art on development. We have opted for a methodology based on surveys, interviews and the study of monographs and catalogues of public and private art institutions to understand the impact of works of art such as paintings, sculptures, mainly made in Congo (Brazzaville). Our aim is to collect data on the condition of creation and promotion of artists, the evolution of supply and demand regarding artistic goods. The population targeted includes painters and sculptors, art workshops and museums in Brazzaville. In addition to demonstrating the place of culture and art in development, the paper puts forward a new approach to African development through art, stressing the need for a cultural and artistic policy in the rest of development.